Life and Work of... Henry Moore - Connolly, Sean (Oxford Heineman Library, 1999)
A picture of the life and work of Henry Moore and his influence on the world of art. It includes: reconstruction artwork of particular scenes from the artist's life; examples of his work at various stages of his life; the life story and photographs of the artist; and a timeline.
Include Colour Illustrations, Glossary and Index
Keywords: England -- Sculptors -- Moore, Henry, 1898-1986